Peran Kepala Desa Dalam Pemberdayaan Perangkat Desa Telukjambe Kabupaten Karawang - Tesa Ariska Sari; Evi Priyanti (Jurnal Ilmiah Wahana Pendidikan, 2022)
The role of the village head in empowering village officials is very necessary for the progress of a village, in terms of service and government by taking the locus of the study of Telukjambe Village to be precise at the village head's office regarding the formation of optimal performance of the apparatus by the Village Head to achieve the vision and mission. The problem of the lack of resources for personnel of productive age who master IT hinders the implementation of the tasks carried out, inadequate facilities, especially in the village office itself, can hamper the service process carried out. So it is necessary to empower the Village Apparatus so that their performance can be maximized. The research method used is a qualitative approach, with data collection techniques through observation, interviews, and documentation. The theory used for analysis and extracting in-depth information related to empowerment uses Suhardono's Theory regarding roles according to social science divided into the Role of the Village Head as Organizer, Role of the Village Head as Facilitator, and Role of the Village Head as Innovator. As a result, the role of the Telukjambe Village Head in the form of empowering the subordinates is carried out quite well. From the recruitment process, formation of structures, placements, and provision of supporting facilities, to those related to ideas or innovations in empowering Telukjambe village officials. Everything has been carried out by the village head although there are obstacles they can still be overcome. The researcher suggests that the empowerment of village officials needs to be optimized but there needs to be a real innovation driving empowerment to achieve success, so far the village apparatus related to services that are so fast, transparent and responsive is a response from the community that can be a reference for village heads to improve the performance of village officials who need to be empowered by fulfillment of needs and the need for training, recruitment of young professional productive age within the scope of the village government to build a digital village as the ideals of the Telukjambe village head.